Isotretinoin-associated possible Kounis syndrome: A case report and a review of other cardiovascular side effects reported in the literature - Murat Akçay; Serkan Yüksel (KARE Publishing, 2019)
Isotretinoin is widely used in the treatment of acne vulgaris and other dermatological diseases. Numerous side effects have been reported in the literature. A myocardial bridge occurs when segments of the coronary artery create an intramyocardial tunnel. Atherosclerotic plaque formation frequently occurs in the segment proximal to a myocardial bridge. Coronary thrombus formation, which is often the cause of myocardial infarction in young patients, can be triggered by many factors. Kounis syndrome is described as acute coronary syndromes associated with allergic or hypersensitivity reactions. This article is a description of the case of a patient predisposed to the development of a thrombus by a myocardial bridge who was successfully treated for coronary thrombosis and which may represent a case of Kounis syndrome associated with isotretinoin use presented in the context of the relevant literature.